Overexpression of CD44 Variant 9: A Novel Cancer Stem Cell Marker in Human Cholangiocarcinoma in Relation to Inflammation - Nattawan Suwannakul; Ning Ma; Raynoo Thanan; Somchai Pinlaor; Piti Ungarreevittaya; Kaoru Midorikawa; Yusuke Hiraku; Shinji Oikawa; Shosuke Kawanishi; Mariko Murata (Hindawi Limited, 2018)
Various CD44 isoforms are expressed in several cancer stem cells during tumor progression and metastasis. In particular, CD44 variant 9 (CD44v9) is highly expressed in chronic inflammation-induced cancer. We investigated the expression of CD44v9 and assessed whether CD44v9 is a selective biomarker of human cholangiocarcinoma (CCA). The expression profile of CD44v9 was evaluated in human liver fluke Opisthorchis viverrini-related CCA (OV-CCA) tissues, human CCA (independent of OV infection, non-OV-CCA) tissues, and normal liver tissues. CD44v9 overexpression was detected by immunohistochemistry (IHC) in CCA tissues. There was a higher level of CD44v9 expression and IHC score in OV-CCA tissues than in non-OV-CCA tissues, and there was no CD44v9 staining in the bile duct cells of normal liver tissues. In addition, we observed significantly higher expression of inflammation-related markers, such as S100P and COX-2, in OV-CCA tissues compared to that in non-OV and normal liver tissues. Thus, these findings suggest that CD44v9 may be a novel candidate CCA stem cell marker and may be related to inflammation-associated cancer development.